RNA sequencing on muscle biopsy from a 5‐week bed rest study reveals the effect of exercise and potential interactions with dorsal root ganglion neurons. Issue 3 (8th February 2022) - McFarland, Amelia J.; Ray, Pradipta R.; Bhai, Salman; Levine, Benjamin D.; Price, Theodore J.
Abstract: Sedentary lifestyle, chronic disease, or microgravity can cause muscle deconditioning that then has an impact on other physiological systems. An example is the nervous system, which is adversely affected by decreased physical activity resulting in increased incidence of neurological problems such as chronic pain. We sought to better understand how this might occur by conducting RNA sequencing experiments on muscle biopsies from human volunteers in a 5‐week bed‐rest study with an exercise intervention arm. We also used a computational method for examining ligand–receptor interactions between muscle and human dorsal root ganglion (DRG) neurons, the latter of which play a key role in nociception and are generators of signals responsible for chronic pain. We identified 1352 differentially expressed genes (DEGs) in bed rest subjects without an exercise intervention but only 132 DEGs in subjects with the intervention. Among 591 upregulated muscle genes in the no intervention arm, 26 of these were ligands that have receptors that are expressed by human DRG neurons. We detected a specific splice variant of one of these ligands, placental growth factor (PGF), in deconditioned muscle that binds to neuropilin 1, a receptor that is highly expressed in DRG neurons and known to promote neuropathic pain. We conclude that exercise intervention protects muscle from deconditioning transcriptomic changes, and prevents changes in the expression of ligands that might sensitize DRG neurons, or act on other cell types throughout the body. Our work creates a set of actionable hypotheses to better understand how deconditioned muscle may influence the function of sensory neurons that innervate the entire body. Abstract : RNA sequencing on muscle biopsies from a 5 week bedrest study shows that an exercise intervention protects muscle from deconditioning transcriptomic changes, and prevents changes in expression of ligands that might sensitize DRG neurons. Our work creates a set of actionable hypotheses to better understand how deconditioned muscle may influence the function of sensory neurons that innervate the entire body.